Impact of T1 slope on surgical and adjacent segment degeneration after Bryan cervical disc arthroplasty - Yang P (Therapeutics and Clinical Risk Management, 2017)
Peng Yang,1 Yongqian Li,2,3 Jia Li,2,3,* Yong Shen2,3,* 1Department of Neurosurgery, Affiliated Hospital of North China University of Science and Technology, Tangshan, 2Department of Orthopedic Surgery, 3Key Laboratory of Orthopedic Biomechanics of Hebei Province, the Third Hospital of Hebei Medical University, Shijiazhuang, People’s Republic of China *These authors contributed equally to this work Background: This retrospective study investigated an association between preoperative T1 slope and surgical and adjacent segment degeneration (SASD) after Bryan cervical disc arthroplasty (BCDA) in patients with cervical degenerative disc disease.Methods: Based on preoperative standing lateral radiographs, 90 patients were classified according to T1 slope that was higher or lower than the 50th percentile (high T1 or low T1, 28 and 62 patients, respectively). Patients were also classified as SASD or non-SASD (38 and 52 patients, respectively) determined by radiographs at final follow-up. Visual analog scale (VAS) and Neck Disability Index (NDI) scores for neck and arm pain were noted, and changes in the sagittal alignment of the cervical spine (SACS), functional spinal unit (FSU) angle, and FSU range of motion (ROM) were also noted. Univariate and multivariate logistic regression analyses were performed to determine the risk factors for SASD.Results: The overall rate of SASD was 42.2% (38/90). The SACS, FSU angle, FSU ROM, and SASD rates of the high T1 and low T1 slope groups were significantly different at the last follow-up. The NDI and VAS scores of the high T1 slope group were significantly greater than those of the low T1 slope. The multivariate logistic regression analysis showed that high T1 slope and endplate coverage discrepancy (ie, residual space behind the prosthesis) were significant risk factors for SASD after BCDA.Conclusion: High T1 slope and endplate coverage discrepancy were associated with SASD after BCDA. Patients with a high preoperative T1 slope have a smaller FSU angle and more neck pain after BCDA. Keywords: Bryan cervical disc arthroplasty, surgical and adjacent segment degeneration, T1 slope, endplate coverage discrepancy, risk factor, clinical outcomes